Applications and Extensions of the Lens Model to Understand Interpersonal Judgments at Zero Acquaintance. (October 2013) - Nestler, Steffen; Back, Mitja D.
The present article reviews current research on the application and extension of the lens model to interpersonal judgments. We first explain how the basic lens model can be used to describe the processes underlying the accuracy of personality judgments at zero acquaintance. Then we outline how this model can be differentiated by assimilating it with research on intuitive and reflective personality judgments, implicit and explicit personality tests, and more or less controlled behavior. We continue by integrating the research on the lens model with research on judgmental errors and knowledge updating. Finally, we describe extensions of the lens model to other interpersonal phenomena at zero acquaintance, such as metaaccuracy and liking. Overall, this review shows that the lens model is a persuasive and flexible framework that can be used to understand interpersonal judgments.